Synthesis and characterization of nickel oxide doped barium strontium titanate ceramics - Banerjee,M. (2012)
Barium strontium titanate (BST) ceramics (Ba0.6Sr0.4)TiO3 were synthesized by solid state sintering using barium carbonate, strontium carbonate and rutile as the precursor materials. The samples were doped with nickel oxide in different proportions. Different phases present in the sintered samples were determined from X-ray diffraction investigation and the distribution of different phases in the microstructure was assessed from scanning electron microscopy study. It was observed that the dielectric properties of BST were modified significantly with nickel oxide doping. These ceramics held promise for applications in tuned circuits.